2005
DOI: 10.1038/sj.hdy.6800711
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variation of the common hippopotamus: evidence for a recent population expansion

Abstract: Mitochondrial DNA control region sequence variation was obtained and the population history of the common hippopotamus was inferred from 109 individuals from 13 localities covering six populations in sub-Saharan Africa. In all, 100 haplotypes were defined, of which 98 were locality specific. A relatively low overall nucleotide diversity was observed (p ¼ 1.9%), as compared to other large mammals so far studied from the same region. Within populations, nucleotide diversity varied from 1.52% in Zambia to 1.92% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 51 publications
(46 reference statements)
0
24
0
1
Order By: Relevance
“…However, the negative and significant Fu’s Fs statistical value observed in Region 1, Region 2 and Region 3 populations provide strong evidence for past population expansion, and rule out the possibility of genetic hitching and background selection, and evolutionary force that produce a pattern similar to population expansion (Fu and Li, 1993; Fu, 1997; Okello et al, 2005). Beneficial genetic variation will generally be accumulated and maintained in a rapidly growing population (Su et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…However, the negative and significant Fu’s Fs statistical value observed in Region 1, Region 2 and Region 3 populations provide strong evidence for past population expansion, and rule out the possibility of genetic hitching and background selection, and evolutionary force that produce a pattern similar to population expansion (Fu and Li, 1993; Fu, 1997; Okello et al, 2005). Beneficial genetic variation will generally be accumulated and maintained in a rapidly growing population (Su et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…Allowing for a large error associated with the estimation of divergence time and based on the molecular clock rate for primate mtDNA of 11.5-17.3% per million years (Vigilant et al 1991), the observed level of sequence divergence indicates that the haplotype groups observed in these primates have been diverging over the past 0.6-1 million years. Thus, these mtDNA polymorphisms seem to date back to the Pliocene-Pleistocene interval when major shifts occurred in the fauna of East African due to increased aridity (Bobe and Behrensmeyer 2004;Heller et al 2008;Okello et al 2008;Okello et al 2005;Storz et al 2002a, b). Subsequently, the mtDNA polymorphisms may have been maintained by habitat heterogeneity in the Tana River landscape as populations in different habitat fragments were isolated from each other.…”
Section: Discussionmentioning
confidence: 95%
“…In Africa, climate change caused major shifts in faunal assemblages during a time interval lasting 5.3 million years during the Pliocene-Pleistocene epochs (deMenocal 2004;Bobe and Behrensmeyer 2004). The genetic imprint of these habitat changes is evident in several mammals in East Africa; buffalo (Heller et al 2008), elephant , hippopotamus (Okello et al 2005) and baboons (Storz et al 2002a, b). During that interval, lower temperatures and increased aridity in East Africa reduced and fragmented tropical forests and left them as isolated patches along major rivers and on high elevation (Bobe and Behrensmeyer 2004).…”
Section: Introductionmentioning
confidence: 97%
“…We used primer pairs Ham1 (5'-CCACCATCAGCACCCAAA-3' and Ham2 (5'-CGAGATGTCTTATTTAAGGGGAA-3') 19 to amplify a 356-bp fragment of the 5' hyper-variable segment of the mitochondrial control region. Amplifications were done in 50 µl reaction volumes containing 2-5 ng of genomic DNA, 50 mM dNTPs, 10 pmol of each primer, 1 unit of Taq DNA polymerase enzyme and 20 mM of 10X PCR reaction buffer containing 1.5 mM MgCl 2 .…”
Section: Dna Amplification and Sequencingmentioning
confidence: 99%